The Importance of Legal Instruments, Culture, and Women’s Participation in Establishing a Fair and Gender-Responsive Family System - Inamah, Inamah; Masnawati, Eli; Hariani, Mila (Journal of Social Science Studies, 2024)
This study maps the implementation of women’s rights protection in the family law system in Indonesia through normative legal analysis, focusing on the influence of social norms and women’s participation in the legislative process and law enforcement. National legal instruments, such as the Marriage Law, the Compilation of Islamic Law, and the Law on the Elimination of Domestic Violence, have become the formal pillars of women’s rights protection. However, social resistance, patriarchal values, and limited access to information and justice often hinder the actualization of women’s legally guaranteed rights. Legal education and gender literacy strengthen women’s position in the family and encourage the creation of a more equitable and gender-responsive family system through knowledge, critical skills, and social value change. Women’s representation in parliament and judicial institutions has a significant influence on shaping more equitable legal regulations and practices, although the number of women in key positions is still limited. Women’s participation, both through formal channels and civil society advocacy networks, strengthens the process of social transformation that is more responsive to gender justice. This study emphasizes the importance of synergy between legal regulations, the recognition of new social norms, and consistent policy advocacy based on women’s experiences. These findings provide a basis for policymakers, academics, and the public to understand the challenges and opportunities for reforming the protection of women’s rights in the family sphere. The combination of legal and social empowerment approaches is a key prerequisite for achieving comprehensive and sustainable protection of women’s rights, so that Indonesia’s family law system truly belongs to all levels of society without exception.